Distanásia em Unidade de Cuidados e a visão de enfermagem: revisão integrativa - Fernandes, Ana Sá (2016)
With the advancement of technology it was possible to prolong the process of life/death of the patient, sometimes prolonging a life without quality. Disthanasia is seen as the artificial prolonging of life and suffering associated with a slow and cruel death, which is done over investment to promote a life without hypotheses, promoting the postponement of death. Materials and Methods: The purpose of this study is to understand what the nurse perception of a Intensive Care Unit in the face of futility. For this integrative review was performed by searching the databases b-ON electronic data, Scielo and EBSCO. This type of revision has the potential to build knowledge and allow the reader to study in a single access different studies. Research was made in October 2013, yielding 16 articles being included only 4 items. Results: It is limitless which sometimes results in suffering and pain with no beneficial purpose. The consensus decision making on futile treat and prolong death is not unanimous. Discussion: The nurses consider that the patient might benefit from his involvement in decision making and that the patient should have an active participation in it. At the end of life, should be provided to the patient palliative care by promoting quality and comfort and die naturally. Conclusions: This type of revision has the potential to build knowledge and allow the reader to study a single access different study. It is considered that in modern times the practice of medical futility tends to occur. The nurses try to intervene but feel their professional limitation so consider should have a more active participation in decision making